Attitude of 5 and 6 Years Old Preschoolers to Cartoon Characters - V.S. Sobkin; I.A. Ryabkova (Культурно-историческая психология)
This work is devoted to the study of the peculiarities of attitude of 5- and 6-year-old preschoolers towards cartoon characters. Hypothesis: There are significant changes in the child's attitude towards cartoon characters, which is manifested both in an increase in the use of his subjective personal assessments of heroes and in a change in the correlations between different personal assessments of characters. Sample: 60 children from 5 to 7 years old (30 girls) we recruited for this study. The 1971 Soviet cartoon "Old Toy" was used as the research material. The study included watching the cartoon by each child. Then he/she was offered a modified method of personal constructs by J. Kelly. The results showed that there are differences in the attitude towards the characters. Six-year-olds use subjective personal constructs more often than objective ones and more often rely on the relationships of the characters. In addition, the structure of the interrelationships of subjective personal constructs differs in five- and six-year-olds. 6-year-old children correlateethical assessments with the actions of the characters, while children of five years evaluate the ethics of the characters according to their characteristics. The results allow us to draw general conclusions about age differences towards cartoon characters in children aged five and six years.